Perancangan Strategi Mitigasi Risiko Rantai Pasok Produk Roti Pada UD. XYZ Dengan Metode House Of Risk (HOR) - Zikri, Muhammad Amar; Zakaria, Muhammad; Jalil, Saifuddin Muhammad (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
UD. XYZ is a Small and Medium Enterprise (SME) focused on bread production. During its production process, it encounters various challenges such as changes in raw material prices, problems in the dough fermentation process, delays in supplier deliveries, and an expiry rate of 8-18% per month. Specifically, a two-part House of Risk (HOR) model and a Supply Chain Operations Reference (SCOR) model are used. First, the SCOR model is used to map the processes in the bakery product supply chain. This data is then loaded into the first stage of the HOR. The next step is to determine the ARP value after evaluating the severity and frequency of incidents. Strategies to manage or mitigate risks are developed using the HOR in the second stage. Twenty risk events and nineteen risk agents were identified at UD. XYZ, with ten priority risk agents identified using a Pareto diagram and mitigation techniques developed. To reduce the likelihood of risk agents appearing in the organization, the second stage of the HOR includes sixteen suggested management tactics.